Beyond the rituals of inclusion: The environment for women and resource governance in Africa's artisanal and small-scale mining sector. Issue 116 (February 2021) - Buss, Doris; Rutherford, Blair; Kumah, Cynthia; Spear, Mary
Highlights: Women's ASM livelihoods are demonstrably important yet including 'women' and gender equality in transnational policy is uneven. Power relations in policy and mining communities shape gendered meanings and practices of ASM and environmental protection. Environmental initiatives in gold ASM in Mozambique and Ghana increased women's exclusion and vulnerability. The Minamata Convention and implementing documents include women primarily as maternal, risky bodies. Women's empowerment and environmental initiatives require situated analyses of gendered political economies. Abstract: This paper considers the apparent confluence of three policy developments: the Sustainable Development Goals, as the latest international commitment to gender equality and women's empowerment; the growing push to formalize the artisanal and small-scale mining sector; and the call to address environmental concerns of ASM through increased regulation, including formalization. Informed by feminist political economy and political ecology scholarship, we consider the kinds of gendered meanings about gold ASM (ASGM) and the environment made possible through the points where formal policy commitments to ASGM, environmental protection and women's inclusion intersect, or fail to intersect. We explore three contexts in which environment narratives have been framed and/or mobilized: the 2014 Minamata Convention on Mercury, followed by two brief case studies examining the consequences of the enforcement of gender-blind environmental initiatives on the livelihoods of women artisanal gold miners in central Mozambique and eastern Ghana. The paper concludes with three recommendations for future work on the intersection of environmental protection programs and women's empowerment agendas for the ASGM sector.